VO2max Berkorelasi Negatif dengan Kemampuan Tahan Nafas (Apnea) - Kukuh Pambuka Putra; Ferry Ferdy Karwur; Nurul Wahidatul Hidayati (Journal of Sport Science and Education, 2020)
Free diving (freedive) depends on the ability to hold the breath (apnea). Apnea is thought to have a correlation with the body's ability to consume oxygen (VO2max). This research aims to study the correlation between VO2max and apnea ability. Subjects in this study were men aged 20-25 years as many as 36 people. VO2max measured using MFT test, while the measurement of apnea ability is represented by the duration of apnea as measured by the duration of sitting still under water. The results of one-way correlation tests were found to be p<0.05, which means there was a correlation between VO2max and apnea duration. While the correlation coefficient of -0.44 shows that the direction of the correlation is negative with the strength of the correlation is weak. From these results it can be concluded that the higher VO2max there is a tendency for apnea ability to be lower.